10.1016/s1544-8800(06)70553-x (CrossRef Listing of Deleted DOIs, 2000)
Aim To describe the clinical characteristics, timing, and long-term outcomes of idiopathic acute pancreatitis (AP) in paediatric inflammatory bowel disease (IBD) after systematic exclusion of secondary causes. Methods We conducted a retrospective single-centre cohort study of paediatric IBD patients followed between January 2018 and December 2024. AP diagnosis and severity were classified according to the North American Society for Paediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) criteria. Patients with drug-induced, metabolic, infectious, genetic, or structural causes were excluded. Clinical, laboratory, imaging, and outcome data were analysed. Results Among 395 paediatric IBD patients, 16 (4.1%) developed AP. After excluding four azathioprine-related cases, 12 patients (3%) were included (50% male; median age 10.6 years). Ulcerative colitis (UC) predominated (67%), with colonic involvement in all cases. Idiopathic AP occurred during active disease in 75% and after IBD-related surgery in 25%. All episodes were mild and resolved with supportive management without complications. Ultrasound showed focal pancreatic inflammatory changes in 58% of patients, predominantly involving the body and tail, while diffuse pancreatic enlargement was reported in 5 patients (42%). Over a median follow-up of 3.7 years, 8/12 patients (67%) developed acute recurrent pancreatitis (ARP), with a median time to recurrence of 9 months. No patients developed pancreatic insufficiency or diabetes. Serum IgG4 levels were negative in all patients. Among those who developed ARP, genetic testing revealed no pathogenic variants. Conclusions Idiopathic AP in children with IBD appeared to be a mild but potentially relapsing condition associated with active intestinal inflammation and colonic disease. Pancreatic function remained preserved despite recurrence, which may be consistent with an immune-mediated gut-pancreas axis. Given the limited sample size, these findings should be considered hypothesis-generating, and prospective multicentre studies are required to confirm these observations and better characterise the underlying pathogenesis.